Synthesis and characterization of UV-curable phosphorus containing hybrid materials prepared by sol-gel technique - KAYAMAN APOHAN, NİLHAN; KARATAŞ, SEVİM (WILEY-BLACKWELL, 2011)
In this study, a series of ultraviolet (UV)-curable organic-inorganic hybrid coating materials containing phosphorus were prepared by sol-gel approach from acrylate end-capped urethane resin, acrylated phenyl phosphine oxide oligomer (APPO), and inorganic precursors. TEOS and MAPTMS were used to obtain the silica network and Ti:acac complex was employed for the formation of the titania network in the hybrid coating systems. Coating performance of the hybrid coating materials applied on aluminum substrates was determined by the analysis techniques, such as hardness, gloss, impact strength, cross-cut adhesion, taber abrasion resistance, which were accepted by international organization. Also, stress-strain test of the hybrids was carried out on the free films. These measurements showed that all the properties of the hybrids were enhanced effectively by gradual increase in sol-gel precursors and APPO oligomer content. The thermal behavior of the hybrid coatings was investigated by thermogravimetric analysis (TGA) analysis. The flame retardancy of the hybrid materials was examined by the limiting oxygen index (LOI); the LOI values of pure organic coating (BF) increased from 31 to 44 for the hybrid materials containing phosphorus (BF-P:40/Si:10). The data from thermal analysis and LOI showed that the hybrid coating materials containing phosphorus have higher thermal stability and flame resistance properties than the organic polymer. Besides that, it was found that the double bond conversion values for the hybrid mixtures were adequate in order to form an organic matrix. The polycondensation reactions of TEOS and MAPTMS compounds were also investigated by (29)Si-NMR spectroscopy. SEM studies of the hybrid coatings showed that silica/titania particles were homogenously dispersed through the organic matrix. In addition, it was determined that the hybrid material containing phosphorus and silica showed fibrillar structure. Copyright (C) 2009 John Wiley & Sons, Ltd.
Keywords: phosphorus; UV-coating; fire resistance; hybrid material; radical polymerization; INORGANIC POLYMER HYBRIDS; EPOXY-RESINS; URETHANE-ACRYLATES; THERMAL-PROPERTIES; COATINGS; SILICON; PHOTOPOLYMERIZATION; NANOCOMPOSITES; FILMS